Intellectual Teamwork: Social and Technological Foundations of Cooperative WorkIntellectual Teamwork: Social and Technological Foundations of Cooperative Work, edited by Galegher Jolene Kraut Robert E. Egido Carmen. Hillsdale, NJ: Erlbaum. 1990, 542 pp., $36.00, paper. - Pentland, Brian T. (Academy of Management Review, 1993)
The article reviews the book ?Intellectual Teamwork: Social and Technological Foundations of Cooperative Work,? edited by Jolene Galegher, Robert E. Kraut and Carmen Egido.